2017
DOI: 10.1155/2017/6934394
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondrial Genome Mutations in Pathogenesis of Carotid Atherosclerosis

Abstract: Mutations of mtDNA, due to their higher frequency of occurrence compared to nuclear DNA mutations, are the most promising biomarkers for assessing predisposition of the occurrence and development of atherogenesis. The aim of the present article was an analysis of correlation of several mitochondrial genome mutations with carotid atherosclerosis. Leukocytes from blood of study participants from Moscow polyclinics were used as research material. The sample size was 700 people. The sample members were diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 16 publications
0
46
2
8
Order By: Relevance
“…A recent study conducted by our group has reported a relationship between mitochondrial functions and atherosclerosis-associated mtDNA mutations investigated on cybrid cell lines carrying various variants of the mitochondrial genome obtained from atherosclerotic patients [110]. Earlier studies of mtDNA obtained from the leukocytes of atherosclerotic patients revealed a correlation between certain mtDNA mutations and atherosclerosis [111][112][113]. Such mutations could be homoplasmic (absence or presence of the mutation) or heteroplasmic (different proportions of mutant allele).…”
Section: Mitochondrial Dysfunction and Mtdna Mutations In Chronic Patmentioning
confidence: 99%
“…A recent study conducted by our group has reported a relationship between mitochondrial functions and atherosclerosis-associated mtDNA mutations investigated on cybrid cell lines carrying various variants of the mitochondrial genome obtained from atherosclerotic patients [110]. Earlier studies of mtDNA obtained from the leukocytes of atherosclerotic patients revealed a correlation between certain mtDNA mutations and atherosclerosis [111][112][113]. Such mutations could be homoplasmic (absence or presence of the mutation) or heteroplasmic (different proportions of mutant allele).…”
Section: Mitochondrial Dysfunction and Mtdna Mutations In Chronic Patmentioning
confidence: 99%
“…This age difference between samples of patients with left ventricular hypertrophy and conventionally healthy participants was not statistically significant. The linkage of mtDNA mutations 652insG, m.5178C>A, m.3336T>C, m.14459G>A, 652delG, m.14846G>A, m.1555A>G, m.15059G>A, m.3256C>T, m.12315G>A and m.13513G>A with atherosclerosis was described earlier by our laboratory researchers [24,[28][29][30][31] . Since LVH has common risk factors with atherosclerosis, it was decided to analyze the relationship of these mutations to mtDNA with left ventricular hypertrophy.…”
Section: Resultsmentioning
confidence: 89%
“…At the same time, two other mutations (m.3336T>C and m.14459G>A) of this enzyme seem to have a protective, stabilizing effect and positively affect mitochondria and cardiac muscle cells. In our preliminary studies, it was found that mutation m.12315G>A, localized in the transfer RNA-Leucine gene (recognition codon CUN), was associated with atherosclerosis [29] . However, in the present study it was found that this mutation has a protective effect on left ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations